Kontribusi Model Contextual Teaching and Learning (CTL) dalam Mata Pelajaran PAK: Upaya Pembinaan Karakter Kristiani pada Remaja Usia 12-15 Tahun - Yogi Supardi; Esti Regina Boiliu (STT Pelita Dunia, 2026)
In the field of Christian Religious Education (CRE), there is sometimes a significant difference between abstract theological teaching and its application in students' lives, especially in children aged 12-15 years, who are experiencing transition and turmoil in their lives. This study focuses on the contribution and effectiveness of the Contextual Teaching and Learning (CTL) Model as a teaching approach to develop and nurture Christian character in children aged 12-15 years through Christian Religious Education. This study uses qualitative data collection methods and a literature review approach with the Bible as the primary source and other literature as secondary sources. Contextual Teaching and Learning is defined as a system that connects students' experiences with their daily lives to create meaning, enabling them to develop dynamic and diverse knowledge. The implementation of Contextual Teaching and Learning in Christian Religious Education involves seven components: constructivism, inquiry, questioning, learning communities, modelling, reflection, and real-world assessment. This model has proven to be very effective in integrating biblical teachings with students' needs, encouraging cognitive, affective, and psychomotor transformation, and helping teachers create a creative learning environment that supports the development of Christian character in adolescents.